The Making of Salty Soy Sauce From Koro Benguk (Mucuna pruriens) (Study of Saline Concentration of Salt Solution and Duration of Maromis Fermentation) - Mulyadi, Arie Febrianto; ., Wignyanto; Hidayah, Eka Yaniar Putri Nur (UNEJ e-Proceeding, 2014)
The objectives of this study were to determine the saline concentration and moromiâs fermentation duration of koro benguk salty soy sauce at best organolepticly and determine consumersâ preferences towards koro benguk salty soy sauce from the best treatment results. The study was conducted using a randomized design method using two factors: the saline concentration (17%; 20%; and 23%) and duration of moromiâs fermentation (2; 3; and 4 weeks). The best treatment results based on the Friedman test was on the saline concentration of 17% and moromiâs fermentation duration was 4 weeks, with the NP value of 1,000; had a preference color level of 5:40 (liked); aroma of 4.30 (rather liked); flavor of 4.55 (rather liked); and viscosityof 5.05 (liked). The obtained protein wasÂ  7.14%; and dissolved solids of 27 brix. Consumersâ preferences towards the best treatment showed that product of koro benguk salty soy sauce was acceptable to consumers. Keywords: Moromiâs Fermentation, Soy Sauce, Saline Concentration, Koro Benguk